Unfolding the Urban Fragments: Walking / Running the City - Sasa Tasic, Mitko Hadzi Pulja, Minas Bakalchev (University of Ljubljana, Faculty of Architecture, Zoisova 2, Ljubljana, Slovenia, 2015)
The city is a living process and a physical artefact. However, contemporary cities are increasingly conceived and imagined as variable programmatic compositions and decreasingly as material artefacts. The physical structure of the city is undergoing a crisis. But, it is exactly the physical texture of the city that contains records of different uses and represents not only a historic-cultural artefact, but also a tool that has the potential to make the city a healthy supportive environment. So, former parts of the city which are presently its marginal zones are not only worthless/obsolete museum pieces, but also potential traces for a new way of conceiving the city and acting in the city. The modern narration starts from the city as a contradiction to nature. This concept still holds today. We are living in the city texture, but we are relaxing ourselves (walking, running) along the periphery or in empty and “green zones” of the cit. Cities have become unsustainable hybrid polarized places: on one hand, we are increasing the development density; while on the other hand, we are widening the free zones. This paper will deal with the inner capacities of the city, its physical traces, and remaining fragments from the aspect of contemporary use in maintenance of the psychophysical condition of the contemporary citizens. The physical structure of the urban fragments is seen as a tool, entity, product of complex social and physical processes that brings numerous values particularly in respect to the most important strategic issues – public health. In the case of the urban fragments of the Skopje city, through morphological decomposition, we will explore the potentials of the different spatial systems of the city as healthy places.
Keywords: Urban fragment, physical structure, spatial practice, running, walking